2006
DOI: 10.1002/dev.20151
|View full text |Cite
|
Sign up to set email alerts
|

The relation of ANS and HPA activation to infant anger and sadness response to goal blockage

Abstract: This study examined the relation of anger and sadness to heart rate and cortisol in 4-month-old infants' (N = 56) response to a goal blockage. The blockage occurred during a contingency learning procedure where infants' response no longer produced a learned interesting event. Anger and sadness were the major emotional expressions to the blockage. The two emotional expressions were differentially related to heart rate and cortisol. Anger was related to increased heart rate, but not cortisol, whereas sadness was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 35 publications
1
55
0
Order By: Relevance
“…The findings extend the positive link between anger expression and persistence in adults and children. In previous studies, greater anger accounted for adults' high, persistent focus on outcomes during goal blockage (Lench & Levine, 2008), whereas anger-prone infants showed more instrumental behaviors (arm pulling) than average infants when blocked during a contingency learning task (Lewis & Ramsay, 2005;Lewis et al, 1992Lewis et al, , 2006. Moreover, in a recent study using the same task (LB) in young children, anger, compared with sadness, was more often followed by problem-solving behaviors; angry children tried more ways to open the transparent box (Dennis et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The findings extend the positive link between anger expression and persistence in adults and children. In previous studies, greater anger accounted for adults' high, persistent focus on outcomes during goal blockage (Lench & Levine, 2008), whereas anger-prone infants showed more instrumental behaviors (arm pulling) than average infants when blocked during a contingency learning task (Lewis & Ramsay, 2005;Lewis et al, 1992Lewis et al, , 2006. Moreover, in a recent study using the same task (LB) in young children, anger, compared with sadness, was more often followed by problem-solving behaviors; angry children tried more ways to open the transparent box (Dennis et al, 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Concerning early development, previous researchers have indicated that angerprone infants exhibited strong approach behaviors toward the goals of the various tasks (Derryberry & Rothbart, 1997;Fox, 1989;Kochanska, Coy, Tjebkes, & Husarek, 1998;Rothbart & Bates, 2006). Anger during goal blockage in infants was associated with perceived control, increased persistent instrumental activities (e.g., arm pulling) to overcome the obstacle, and increased positive emotions (e.g., interest and joy) once the obstacle was removed (Lewis & Ramsay, 2005;Lewis, Ramsay, & Sullivan, 2006;Lewis et al, 1992). Kearney (2004) found that high anger-prone infants at seven and nine months of age were more likely to complete the frustrating task and were described by their mothers as knowing what he or she wants and getting it.…”
Section: Introductionmentioning
confidence: 99%
“…It spontaneously appears in infancy (1,2), is effectively universal in its distribution across cultures and individuals (3,4), and has a species-typical neural basis (5). To understand the evolutionary biology of anger, however, it is also important to characterize its evolved function-that is, what (if anything) was anger engineered by natural selection to accomplish?…”
mentioning
confidence: 99%
“…Low activity toward goals, increased cortisol response, expressions of sadness or fear, and behavioral signals of helplessness or a need to move away from a stimulus index withdrawal emotion (Buss et al, 2003; Lewis, Ramsay, & Sullivan, 2006). Withdrawal tendencies need not require self-initiated movement away from stimuli in non-locomoting infants, only the ability to vocalize distress and display sadness.…”
Section: What Is the A/w Model?mentioning
confidence: 99%